2021
DOI: 10.1002/aelm.202000905
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Microwave Device Fabrication on Low‐Temperature Crystallized Ba0.5Sr0.5TiO3 Thin Films by an Alternating Deposition and Laser Annealing Process

Abstract: This article demonstrates a method to fabricate crystalline Ba0.5Sr0.5TiO3 (BST) thin films at a lower temperature of ≈300 °C using an excimer laser by an alternating depositing and annealing process. Firstly, a BST thin film with a thickness of ≈120 nm is deposited at 300 °C (laser energy of ≈2 J cm−2) and subsequently laser annealed (66 mJ cm−2) at 300 °C. This process is repeated five times to obtain thicker device quality films. XRD patterns, TEM, Raman, and UV–Vis–NIR spectroscopy confirm that phase forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…28 The enhanced performance of visible-light-dried ECD may be due to the absorption band of WO 3 (band gap of 2.7 eV) in the visible region (WO 3 visible catalyst), which can absorb more light and improve its chemisorption of oxygen and evaporation of H 2 O molecules. 29,30 The improved chemisorbed oxygen improves the oxidation states of WO 3 and evaporation of water molecules, which results in higher optical modulation and long-life stability in ECDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…28 The enhanced performance of visible-light-dried ECD may be due to the absorption band of WO 3 (band gap of 2.7 eV) in the visible region (WO 3 visible catalyst), which can absorb more light and improve its chemisorption of oxygen and evaporation of H 2 O molecules. 29,30 The improved chemisorbed oxygen improves the oxidation states of WO 3 and evaporation of water molecules, which results in higher optical modulation and long-life stability in ECDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When irradiating the material, laser energy is absorbed and the surface layer of the material is heated to a high temperature at a large heating rate, which are always accompanied by the origination of high stress and stress gradient. The high temperature together with the stress drive the material to evolve, like crystallinity improvement, [12][13][14] texture evolution, [15] voids elimination, [16] and recrystallization. [17] In the present study, according to the material analysis (Figure 2 and 3), the metastable as-deposited gold film recrystallized after laser irradiation.…”
Section: Effect Of Pulsed Laser Irradiation On the Microstructure Of ...mentioning
confidence: 99%
“…[6,8] And this may bring about some detrimental changes, e.g., weakening the bonding between gold film and the substrate, and leading to grain boundary cracks. [8] Laser irradiation is a versatile mean in the machining and processing of materials [9][10][11] and was applied to regulate both the microstructure [12][13][14][15][16][17] and stress [17][18][19][20] of films and coatings. Goud [12] studied the laser irradiation of Ba 0.5 Sr 0.5 TiO 3 thin films, and the results showed that laser irradiation can turn the film deposited at low temperature from amorphous to crystalline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their high performance, microwave dielectric ceramics are usually treated as the main dielectric function materials in satellites, terminals, base stations, and other communication devices. [ 14–17 ] Microwave ceramic components, which has become a research hotspot worldwide, can better meet the demand for portability, miniaturization, and integration of communications equipment. [ 18,19 ] Near‐zero CTE ensures that DRAs operate within the variable temperature.…”
Section: Introductionmentioning
confidence: 99%